Negotiating Voice: Gendered Marginalization and Co-Cultural Performance in American Talk Shows - Dr. Sobia Ilyas (Indus Journal of Social Sciences, 2025)
This study critically examines female marginalization on American talk shows, focusing on The Late Show with Stephen Colbert through the interviews of Nicki Minaj (2018) and Lady Gaga (2021). Integrating Co-Cultural Theory (CCT) with Feminist Critical Discourse Analysis (FCDA) and Conversation Analysis (CA), the research investigates how female guests navigate dominant conversational norms to achieve assimilation, maintain visibility, and assert agency within male-dominated media spaces. FCDA exposes the gendered and ideological framing embedded in the interviews, while CA captures micro-level interactional dynamics, including interruptions, topic shifts, and humor that reinforce the host’s discursive authority. Findings reveal that, despite moments of apparent empowerment, female guests operate within structurally constrained arenas that privilege male authority and entertainment-driven agendas, necessitating strategic negotiation to sustain presence and voice. The study underscores talk shows as highly controlled public spheres that normalize gendered marginalization while highlighting the nuanced strategies women employ to resist erasure. Future research could examine how gender, ethnicity, and other co-cultural identities are navigated across diverse talk-show formats, further illuminating subtle discursive practices that shape visibility, power, and agency in mediated spaces.